(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article covers the socio-political life of the khanates of Central Asia on the eve of the invasion of the Russian Empire, the attitude of the population to the policy of governance on the basis of the works of local historians and Russian politicians. Revolts in the city of Tashkent in the second half of the XIX century and their consequences are described.